Measuring the Level of Financial Reporting Quality of Commercial Banks Listed On the Iraq Stock Exchange for The Period (2016-2023) - Hayder Mahdi Allawi (International Forum of Researchers and Lecturers, 2025)
The aim of the research is to measure the level of financial reporting quality for a sample of banks listed in the Iraq Stock Exchange due to their great importance as they are the main source for making various decisions for users and stakeholders, as their high quality contributes to making sound decisions and increasing confidence in dealing with economic units. To achieve the research objective, the financial data of the research sample, represented by five banks listed in the Iraq Stock Exchange for the period from 2016 to 2023, were analyzed. The accounting conservatism index was used as a proxy for the quality of financial reports according to the (MTB) model, the ratio of the market value of equity to its book value. The results showed a discrepancy between the banks in the research sample in the level of quality of financial reports according to the conservatism index.